Campus landscape preferences : a favorable planting composition in study area / Norizan Mt Akhir and Siti Rasidah Md Sakip - Norizan, Mt Akhir; Siti Rasidah, Md Sakip (Universiti Teknologi MARA, Perak, 2017)
The landscape is an important part of campus as source of beautification and healthy environment The landscape preferences in campus usually explore by asking the participants to rate their most favourable landscape scene. This study aims to evaluate the favorable planting composition in students} study area. The objectives of the study are to identify the patternof planting composition in the campus and to relate the impact of composition towards utilising the outdoor study area by students. Throughout the literature review, this research generates briefly discussion on the relationship between planting composition and students learning behavior in the study area.